If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7 + -5x + 4 = 2x + 4 Reorder the terms: 7 + 4 + -5x = 2x + 4 Combine like terms: 7 + 4 = 11 11 + -5x = 2x + 4 Reorder the terms: 11 + -5x = 4 + 2x Solving 11 + -5x = 4 + 2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2x' to each side of the equation. 11 + -5x + -2x = 4 + 2x + -2x Combine like terms: -5x + -2x = -7x 11 + -7x = 4 + 2x + -2x Combine like terms: 2x + -2x = 0 11 + -7x = 4 + 0 11 + -7x = 4 Add '-11' to each side of the equation. 11 + -11 + -7x = 4 + -11 Combine like terms: 11 + -11 = 0 0 + -7x = 4 + -11 -7x = 4 + -11 Combine like terms: 4 + -11 = -7 -7x = -7 Divide each side by '-7'. x = 1 Simplifying x = 1
| 6(6+3n)=2(n-6) | | 5(x+3)-2=x+13 | | 6x-7=33-4x | | 3z-8-z+4=0 | | 30=2-4m | | -20=3y-2 | | 3(t-2)+5t=4(2t+3)-11 | | 13a=-39 | | n(4n+3)=0 | | 2x+15+3x+x-27=180 | | 4(4x+1)=4x-9x | | 28-5k=-4k | | 5-y=9-8 | | 6(x+2)=4x-12 | | 2x+6y=52 | | (w)(w+4)+15=(w+3)(w+5) | | 4x-2y-25=0 | | -(m-6)=25 | | 4n^2+11=7n | | 6x^4+15x^3+22x^2+40x+16=0 | | 6+3n=n+4 | | 4x+5y=x+2y+10 | | 6(x+2)=4-12 | | 5(6x+2)+3=30x+13 | | 5n^2+6=8 | | 6x-7=7x-2x | | r+7=-4r+6r+13 | | x*1.56=39 | | 2x^2-15x+63=0 | | 8x+6y=64 | | -x^2+19x-90=0 | | 30*x=1.56 |